ANALISA REVALUASI VALUTA ASING DALAM PENYUSUNAN LAPORAN KEUANGAN UNIT AKUNTANSI KUASA BENDAHARA UMUM NEGARA-DAERAH (UAKBUN-D) - Situmorang, Dokman Marulitua; As’adi, Amin (Jurnal Manajemen Retail Indonesia (JMARI), 2022)
This study aims to provide an overview of the foreign exchange revaluation process in the preparation of financial statements of the State-Regional General Treasurer (UAKBUN-D) at KPPN Jakarta III. The foreign currency revaluation process at the KPPN is carried out every quarter starting when the preparation of the semester I financial statements. Post revaluation includes cash accounts in the KPPN cash in the treasury for foreign currency expenditures, and debt to third parties (returns) on the KPPN balance sheet. The foreign exchange revaluation process is carried out using an application assistance, namely the State Treasury and Budget System (SPAN) in the General Ledger (GL) module which is held by the verification and accounting section (Vera). This research uses descriptive qualitative research methods. The result of this research is that foreign exchange revaluation at KPPN Jakarat III is carried out in order to translate monetary assets in foreign currency into rupiah as reporting currency so that it can be presented reliably in the Financial Statements of UAKBUN-D KPPN Jakarta III. The process of the revaluation process is carried out using the assistance of the SPAN application at 3 posts, namely, Cash at the KPPN, Cash in the Expenditure Treasurer and Debt to Third Parties.